Electrocardiogram Profile in Children with Dengue Infection at Dr. Hasan Sadikin General Hospital and Bandung City Hospital - Sakinah Binti Shabbir Hussain; Rahmat Budi Kuswiyanto; Januarsih Iwan (Althea Medical Journal, 2016)
Background: Dengue is a mosquito-borne infection which causes many manifestations on the organs, mainly heart. According to the histopathological analysis in heart, there is a direct action of dengue virus towards myocardium. This study was an initial study of cardiac involvement in dengue infection using electrocardiogram as a measurement tool. Methods: This study was a descriptive cross-sectional study and data collection were performed consecutively. A total of 17 children was taken which had been diagnosed with dengue infection according to World Health Organization criteria and had fulfilled inclusion and exclusion criteria of this study in Dr. Hasan Sadikin General Hospital and Bandung City Local Hospital. Once informed consent was obtained, the electrocardiogram procedure was performed according to standard electrocardiogram procedure in pediatrics. Data were analyzed by a pediatric cardiology consultant. Data were interpreted based on the electrocardiogram characteristics according to the type of dengue infection.Results: P wave amplitude was getting shorter as the severity of dengue infection increased. P wave duration increased slightly with increased severity of dengue infection. There was a significant increase in PR interval as the severity of dengue infection increased. The same was also true for ST and QTc wave.Conclusions: The pattern of electrocardiogram profile in children with dengue infection were within normal range. [AMJ.2016;3(4):629–32] DOI: 10.15850/amj.v3n4.950